Исследование процесса пиролиза отходов биомассы в плотном слое - Губинский, М. В.; Шишко, Ю. В.; Шевченко, Г. Л.; Усенко, А. Ю.; Федоров, С. С.; Кремнева, Е. В. (НТУ "ХПИ", 2008)
The object of researches was the biomass pyrolysis process. It was creative the experimental installation for carry out of pyrolysis with getting heat energy. The pyrolysis in the dense layer with getting pyrolysis gas and carbon was realized. As results of carry out researchers was definite the rational air consumption, the range of working temperature and length of pyrolysis.
Keywords: топливо; эмиссия парниковых газов; мелкодисперсные отходы; пиролизный газ